The effect of an objective weighting of the Global Food Security Index's natural resources and resilience component on country scores and ranking - Hendriks, Sheryl L. (University of Pretoria, 2021)
Mini Dissertation (MScAgric (Agricultural Economics))--University of Pretoria, 2021.